Reactive dicarbonyl compounds cause Calcitonin Gene-Related Peptide release and synergize with inflammatory conditions in mouse skin and peritoneum - Becker, Anna; Auditore, Andrea; Pischetsrieder, Monika; Meßlinger, Karl; Fleming, Thomas; Reeh, Peter; Sauer, Susanne (Journal of Biological Chemistry, 2020)
The plasmas of diabetic or uremic patients and of those receiving peritoneal dialysis treatment have increased levels of the glucose-derived dicarbonyl metabolites like methylglyoxal (MGO), glyoxal (GO), and 3-deoxyglucosone (3-DG). The elevated dicarbonyl levels can contribute to the development of painful neuropathies. Here, we used stimulated immunoreactive Calcitonin Gene–Related Peptide (iCGRP) release as a measure of nociceptor activation, and we found that each dicarbonyl metabolite induces a concentration-, TRPA1-, and Ca2+-dependent iCGRP release. MGO, GO, and 3-DG were about equally potent in the millimolar range. We hypothesized that another dicarbonyl, 3,4-dideoxyglucosone-3-ene (3,4-DGE), which is present in peritoneal dialysis (PD) solutions after heat sterilization, activates nociceptors. We also showed that at body temperatures 3,4-DGE is formed from 3-DG and that concentrations of 3,4-DGE in the micromolar range effectively induced iCGRP release from isolated murine skin. In a novel preparation of the isolated parietal peritoneum PD fluid or 3,4-DGE alone, at concentrations found in PD solutions, stimulated iCGRP release. We also tested whether inflammatory tissue conditions synergize with dicarbonyls to induce iCGRP release from isolated skin. Application of MGO together with bradykinin or prostaglandin E2 resulted in an overadditive effect on iCGRP release, whereas MGO applied at a pH of 5.2 resulted in reduced release, probably due to an MGO-mediated inhibition of transient receptor potential (TRP) V1 receptors. These results indicate that several reactive dicarbonyls activate nociceptors and potentiate inflammatory mediators. Our findings underline the roles of dicarbonyls and TRPA1 receptors in causing pain during diabetes or renal disease.
CRIS-Team Scopus Importer:2020-05-26